WHO IS MY NEIGHBOUR? EUROPEAN IDENTITY AND THE REIMAGINATION OF ETHICAL POLITICS IN THE CONTEXT OF THE MIGRATION CRISIS OF 2015/2016 (Journal for Freedom of Conscience (Jurnalul Libertății de Conștiință), 2022)
Identity, Christian ethics and migration are often seen as descriptive concepts of dissentive qualities involving static, perene aspects versus dynamism and change. However, the opposite can be argued when looking at identity as a flowing, organically changing notion in contrast to a rigid and inflexible migration concept all of those being embedded in an ideological context of Christian and/or humanistic politics. This article highlights the points of intersectionality between national and European identity and analyzes the political impact of the recent migration waves to Europe on the process of identity formation within the European Union. It also describes the identity conflicts among European citizens of diverse nationalities and, at the same time, the phenomenon of othering between Europeans and refugees.